A membrane-distal segment of the integrin alpha IIb cytoplasmic domain regulates integrin activation. - Ginsberg, M; Yaspan, B; Forsyth, J; Ulmer, T; Campbell, I; Slepak, M (2001)
Previous evidence suggests that interactions between integrin cytoplasmic domains regulate integrin activation. We have constructed and validated recombinant structural mimics of the heterodimeric alpha(IIb)beta(3) cytoplasmic domain. The mimics elicited polyclonal antibodies that recognize a combinatorial epitope(s) formed in mixtures of the alpha(IIb) and beta(3) cytoplasmic domains but not present in either isolated tail. This epitope(s) is present within intact alpha(IIb)beta(3), indicating that interaction between the tails can occur in the native integrin. Furthermore, the combinatorial epitope(s) is also formed by introducing the activation-blocking beta(3)(Y747A) mutation into the beta(3) tail. A membrane-distal heptapeptide sequence in the alpha(IIb) tail ((997)RPPLEED) is responsible for this effect on beta(3). Membrane-permeant palmitoylated peptides, containing this alpha(IIb) sequence, specifically blocked alpha(IIb)beta(3) activation in platelets. Thus, this region of the alpha(IIb) tail causes the beta(3) tail to resemble that of beta(3)(Y747A) and suppresses activation of the integrin.